Edward Everett Hayden family papers - Hayden, Edward Everett, 1858-1932.; Hayden, Alfred, 1894-; Hayden, Herbert B. (Herbert Bainbridge), 1885-1969.; Hayden, Mary Bainbridge, 1895-; Hayden, Reynolds, 1883-; Hayden, William, 1795-1880.; Reynolds, Joseph Jones, 1822-1899.
Correspondence, diaries, journals, notebooks, financial materials, photographs, and other papers pertaining to Hayden's naval and scientific careers and to the Hayden family. Topics include Hayden's position as secretary of the National Geographic Society (1895-1897), his work in charge of time service and chronometers at the United States Naval Observatory (1902-1910), his command of the U.S. Naval Station at Key West, Fla. (1910-1915), his various inventions and patents, and his scientific research in hydrography, meteorology primarily relating to hurricanes, and timekeeping.
Includes family papers providing documentation of military family life in the late 19th and early 20th centuries. Papers of Edward Hayden's children document Reynolds Hayden's service with American military forces in the Boxer Rebellion; Herbert B. Hayden's years as a cadet at the United States Military Academy, West Point, N.Y.; Alfred Hayden's school years at Staunton Military Academy, Staunton, Va., and the Virginia Military Institute; and Mary Bainbridge Hayden's career as a journalist especially her coverage of Herbert Hoover's presidential campaign of 1928. Also includes the papers of Edward Hayden's grandfather, William Hayden, postmaster of Boston (Mass.), whose correspondents include Jacob Collamer, John Davis, and Daniel Webster; and of Edward Hayden's father-in-law, Joseph Jones Reynolds, relating especially to his command of military districts in Louisiana and Texas during the Reconstruction.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
U.S. naval officer and scientist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Collamer, Jacob, -- 1791-1865.; Davis, John, -- 1787-1854.; Hoover, Herbert, -- 1874-1964.; Webster, Daniel, -- 1782-1852.; Hayden family; United States. -- Navy -- Military life; United States. -- Navy -- Officers; National Geographic Society (U.S.); Staunton Military Academy; United States Military Academy; United States Naval Observatory; Virginia Military Institute; Astronomical observatories -- Washington (D.C.); Chronometers; Geography -- Societies, etc; Hurricanes -- Research -- United States; Hydrography -- Research -- United States; Meteorology -- Research -- United States; Military education -- New York (State) -- West Point; Military education -- Virginia; Navy-yards and naval stations -- Florida -- Key West; Postmasters -- Massachusetts -- Boston; Presidents -- United States -- Election -- 1928.; Reconstruction (U.S. history, 1865-1877) -- Louisiana; Reconstruction (U.S. history, 1865-1877) -- Texas; Timekeeping -- Research -- United States; Women journalists; China -- History -- Boxer Rebellion, 1899-1901.; Key West Naval Station (Fla.); Naval officers; Scientists